AI in Consumer Protection: a Bibliometric Analysis: AI dalam Perlindungan Konsumen: Analisis Bibliometrik - Muhammad, Fadil; Bagus Edhita Praja, Chrisna; Maitsaa’ Jaudah, Tsuroyyaa (Universitas Muhammadiyah Bima, 2025)
This study explores global research trends on the role of artificial intelligence (AI) in consumer protection law through bibliometric analysis. The research data is taken from the Scopus database with the keywords